O controle de constitucionalidade difuso da súmula vinculante como instrumento hábil a garantir o direito fundamental de acesso à justiça - Debortoli, Karina (2018)
The topic of this paper is the analysis of the possibility of having the decentralized or diffuse control of constitutionality of the binding precedent as an effective mechanism to safeguard the fundamental right of access to justice. The deduction reasoning was used as the methodology and the bibliographic review, as the research technique, which proved to be the most adequate, for it enables analysis of vast doctrinal material on the topic. The theoretical development of the study is based on the reference of the constitutional jurisdiction developed by Hans Kelsen as well as his theory on the legal pyramid and the need of observing the fundamental act at the moment of creation of infra-constitutional acts, using the constitutionality control. Such ideas, together with the concepts of the fundamental right of access to justice and of normative act, along with the study of the formation of the binding precedent, make it possible in the end to understand the nature of the normative act of the binding precedent and subsequently, its submission to the diffuse control of constitutionality as a way to safeguard access to justice.